EFFECTS OF PUBLIC DEBT CRISES ON LIFE EXPECTANCY: AN EMPIRICAL INVESTIGATION FOR SUSTAINABLE DEVELOPMENT OF NIGERIA - Popoola, Timothy Oladayo; Mohammed, Oluwaseyi A.; Aliyu, Victoria Ohunene; Peter, Olayinka Adeyemi; Amasa, Mukhtar Olaide; Egem-Odey, Benjamin; Hamza, Ahmed; Ogunlade, Maria Funmilayo (African Journal of Social and Behavioural Sciences, 2025)
Nigeria faces persistent public debt crises, alongside one of the lowest life expectancy levels in Sub-Saharan Africa. Accordingly, this study empirically estimates the effect of public debt on life expectancy in Nigeria. Covering the period from 1981 to 2020, the study employs the Johansen co-integration approach. The findings indicate a negative and significant long-run relationship between Nigeria’s external public debt and life expectancy. Conversely, domestic public debt is statistically significant and contributes positively to life expectancy in Nigeria in the long run. Based on these results, the study recommends reducing external debt while ensuring that domestic debt is properly monitored and safeguarded against misappropriation to enhance life expectancy at birth in Nigeria. Nigeria’s governments could also finance their budget deficits with domestic borrowing. However, they should ensure that such funds are allocated to priority projects that have the capacity to deepen the economy and improve citizens' well-being.